Equisetum ×moorei Newman (Equisetaceae) – a ‘new’ nothotaxon in the Polish flora - Kalinowski, Paweł; Sliwinska, Elwira; Kruk, Jerzy (Biodiversity: Research and Conservation, 2016)
To investigate present and historical distribution of Equisetum ×moorei in Poland and its habitat requirements, field studies at sites of potential occurrence of this hybrid taxon as well as literature and herbarium search were performed. As a results of these investigations, E. ×moorei was found at five contemporary and at a few historical localities in the present territory of Poland. Since the Equisetum populations near Olkusz (S Poland) showed phenotype similar, to some extent, to triploid hybrid E. ×ascendens, we performed nuclear DNA content analysis of these populations. However, it turned out that the investigated individuals belonged to a diploid taxon that can be ascribed to E. ×moorei.